Thermal and energy performance of a user-responsive microalgae bioreactive façade for climate adaptability. (August 2022) - Talaei, Maryam; Mahdavinejad, Mohammadjavad; Azari, Rahman; Haghighi, Hadi Motevali; Atashdast, Ali
Graphical abstract: Highlights: The microalgae panel has an appreciable effect on daylight and solar energy control. The panel controls thermal load by interactively absorbing solar energy and increasing in microalgae culture. Thermal and energy performance of the user-responsive panel is assessed. The shading level interactively changes by users in short time through a remotely-controlled system. As green, smart façade, this system is a novel way towards energy efficient architecture. Abstract: As a recent trend in the energy-efficient architecture, microalgae bio-reactive façades can control buildings' thermal loads by the responsiveness to solar radiations and adaptive variations in culture density. Although these smart systems can provide adaptable shading during the year, they cannot meet the varying thermal comfort needs of building users in a short time because the microalgae medium's culture remains almost unchanged during the day. This paper reports on an innovative method that helps microalgae bioreactive façade respond to solar radiation and users' thermal needs in a short time. To achieve it, a smart window panel will be introduced, which contains two remotely-controlled adjustable bioreactors which can regulate the algae medium in height based on the users' thermal needs. This novel panel can serve as a bio-adaptable sunshade integrated with the building facade. Thus, the internal building thermal loads can be adjusted via the height of the bioreactor façade. Experimental and simulation research was conducted to compare the thermal performance of bioreactor facades at different microalgae medium height levels in the BSk climate zone. The results indicate that indoor and outdoor temperature differences for full, ¾, ½, and ¼ medium height level every 15-minute time interval are 12.55, 11.50, 10.87, and 6.53, respectively, indicating that the full-height level has the most influence to control the thermal load of the system. According to the results, the bioreactor façade with adjustable medium height greatly impacts building thermal control in a short time.